Using the Rasch model to grade a test Teacher's skills in identifying learning difficulties in students with learning disabilities - Boubou, Mounzer; Charrouf, Ansab; Slman, Noura (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aimed to arranging the items of the teacher's skills test in identifying learning difficulties. The test was made up of 60 items and The sample of the study included (300) teachers. The statistical study showed that the assumptions of the Items response theory (IRT) have been achieved as the results of the test scale after omitting 5 items showed that the test is constant. Stability vocabulary coefficient was /0.97/ and Stability of individuals coefficient was /0.68/. It turns out that the test covered how difficult vocabulary, vocabulary difficulty value ranged between/2.48/and/2.05/logt. And evaluated the ability of individuals between 1.26 and 2.1.13 logitech. The values of all vocabulary were included in a statistical value corresponding to the Rush model.